Body of writing figuring desire in Spanish American literature - Prieto, René (Duke University Press, 2012)
Introduction -- Julio Cortázar's perpetual exile -- More than meets the I: Guillermo Cabrera Infante's La Habana para un Infante difunto -- The excremental vision of Gabriel García Márquez -- The degraded body in the work of Severo Sarduy -- Rewriting the body: renewal through language in the work of Rosario Castellanos -- The body of pleasure in Tununa Mercado's Canon de alcoba